“Seeing Law in Terms of Music” A Short Essay on Affinities between Music and Law - Arban, Erika (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2017)
It is often believed that law and the arts have very little in common, since law is perceived as a rather formalistic and inaccessible subject incapable of eliciting emotions in the same way as the arts. This article, however, aspires to offer a different picture : by exploring music in its interconnectedness with law, it condenses the main arguments discussed by literature to ultimately show that law and music may reveal, after all, surprising affinities, so that some thought-provoking parallels between them can be made. Similarly, the paper strives to find points of connection between law and music in order to show the profound resiliency of law as an academic discipline. Finally, the paper advances the idea that the unbridgeable distance between the two disciplines exists (partially) in appearance only and that, in spite of its allegedly technical nature, law is a very flexible field of knowledge whose intellectual structure can influence and inform other creative processes.